Where No Man Has Gone Before: The Future of Sustainable Development in the Comprehensive Economic and Trade Agreement and New Generation Free Trade Agreements - Hush, Emily (Columbia Journal of Environmental Law, 2019)
It is no secret that the planet is warming and that humans have had something to do with it. Over the last one hundred and fifty years, the global average concentration of carbon dioxide in the Earth’s atmosphere has increased to unprecedented levels and continues to rise. As the climate becomes warmer, the world will face ocean acidification, sea level rise, decreasing biodiversity, and more extreme weather events. At the end of the twentieth century, many nations recognized that climate change is a global phenomenon requiring cooperative action, and began to seek international solutions to prevent disastrous warming and to mitigate unavoidable impacts. Sustainable development is central to this international response to climate change. International agreements like the United Nations Framework on Climate Change and the Paris Agreement are indispensable to furthering sustainable development worldwide. However, the complexity of such large multilateral agreements presents a barrier to effective negotiations. The Paris Agreement boasts one hundred and ninety-seven parties. Because the needs and interests of nation-states are so varied, achieving consensus among many participants leads to either less binding or less ambitious agreements. For example, the emissions reduction commitments (“nationally determined contributions”) made by the Paris signatories are technically binding, but toothless, because the Agreement does not provide any enforcement mechanisms. Yet, even if every nation fulfills its commitment, we will fail to reach the Agreement’s goal of limiting warming to two degrees Celsius. One way to strengthen consensus among many nations is to build on smaller coalitions and partnerships. For example, the forty-four states and observers that make up the Alliance of Small Island States leveraged their joined voices to obtain the inclusion of an additional 1.5 degrees Celsius goal in the Paris Agreement. Similarly, bilateral free trade agreements (“FTAs”) provide important opportunities for aligning international objectives on climate change and sustainable development. FTAs can promote sustainable development by granting states a robust right to regulate in the public interest. This right determines what regulatory actions governments may take that impact investments without violating investors’ rights; it is central to the successful implementation of an agreement’s sustainable development objectives. The European Union (“EU”) in particular has embraced FTAs as a vehicle for sustainability. In recent years, the EU has negotiated a wave of new FTAs that strive to bring sustainable development to the forefront of bilateral trade. These so-called New Generation FTAs seek to deepen cooperation between nations not only on non-tariff barriers to trade, as traditional FTAs do, but also in areas of social and environmental import. This goal is primarily accomplished by shielding the parties’ right to regulate, and by expanding and heightening the specificity of provisions on labor, environmental protection, and sustainable development. Although these provisions do not mention climate change specifically, their ability to facilitate the development of innovative sustainable development policies will necessarily impact the transition to a low-emission world. In October 2016, as part of this New Generation, the EU and Canada (collectively, “the Parties” or individually, “Party”) signed the Comprehensive Economic and Trade Agreement (“CETA”). CETA was designed to strengthen the Parties’ economic relationship by reducing barriers to trade and investment. The agreement is now provisionally in force pending ratification. CETA introduces a new Investor Court System (“ICS”) featuring a permanent judicial body (the “ICS Tribunal”), includes an expansive chapter on trade and sustainable development, and insistently asserts the Parties’ right to regulate in the public interest. This Note investigates what protection the right to regulate might provide to the Parties when defending their regulatory measures against investor claims brought under CETA. It asks whether CETA will successfully avoid the chilling effect that investor-state arbitral awards have typically had on the exercise of state police powers. It argues that the protection that the right to regulate explicitly provides to state environmental regulation implicitly extends to state action taken in furtherance of sustainable development, because sustainable development encompasses environmental protection. It concludes that while CETA’s provisions on sustainable development have the potential to provide broad protection to state regulations, future agreements must build on this foundation to secure their continued implementation. Part II explains the concepts of sustainable development and of the state’s right to regulate. It introduces the reader to New Generation FTAs and demonstrates how CETA fits into that mold. It concludes with a look at each Party’s objectives for CETA. Part III presents the legal framework that the ICS Tribunal will apply when it interprets CETA. It explains Article 31 of the Vienna Convention on the Law of Treaties (“Vienna”), and gives an overview of the most important international cases applying that Convention to the right to regulate and to sustainable development. It applies the resulting interpretive principles to CETA. By reproducing the analysis that the ICS Tribunal may employ to evaluate an investor claim under CETA, this Note identifies arguments that the Parties could raise to defend their right to regulate. Part IV recommends how the Parties can broaden and strengthen the content of their regulatory right, as well as how future FTAs can build on CETA’s achievements. Part V concludes that CETA constitutes an important first step towards advancing sustainable development through the exercise of the right to regulate.